A Patient With Cervical Herniated Nucleus Pulposus (HNP) - TBL Format - Maria Sheakley; Danielle Royer; Aidi Yin; Davendra Sharma; Eniton Odutola (Association of American Medical Colleges, 2013)
Abstract Introduction This resource is a team-based learning (TBL) module intended for first-year medical students. It is an integrated case module that includes material from several basic sciences disciplines, including gross anatomy, histology/cell biology, radiographic anatomy, cell physiology, and behavioral science. By the conclusion of this module, students will be able to describe the normal anatomical structures of the vertebral column, spinal cord, and spinal nerves and identify these structures on medical images. In addition, they will be able to recognize the signs and symptoms of a cervical herniated nucleus pulposus and identify this clinical presentation on an MRI. Finally, they will understand how to organize and record this type of patient history and physical. Methods This case was written to be used in a TBL format. TBL cases utilize a specific written format and method of facilitating to produce very effective small-group and class discussion. The TBL session consists of the following parts: individual Readiness Assessment Test (iRAT), group RAT (gRAT), student-faculty discussion of RAT, break, group application exercise, and student-faculty discussion of group application exercise. This session requires approximately 2 hours to complete. Our TBL sessions are graded, and the scores are recorded as a part of the class grade. At the first session of each semester, the students form groups of six and vote for the grading scheme that will be utilized. The iRAT and gRAT grade weighting is decided by the students, and at our institution, the clinical application exercise is graded but not officially recorded. Results We have run this case module three times, and it has always generated excellent discussion and student praise. The students particularly like the integrative nature of the case, as it is facilitated with a gross anatomist, cell biologist/histologist, radiologist, and behavioral scientist. Discussion Our facilitators are content experts, and this adds a level of finesse to the facilitation that would be more difficult to achieve without the content knowledge. However, we believe a very skilled facilitator without content knowledge could run this session as well.